Rethinking the Concepts of Subsumption, Surplus Value and Audience Labour in Digital Capitalism (Global Journal of Human-Social Science, 2020)
This article analyzes the concept of subsumption concerning the evolution of labour and surplus value, focusing on the so-called audience labour as that constant users' digital and social media activity of contemporary capitalism. For some authors, this activity directly produces surplus value in abstract and should be considered as productive labour. On the conclusions, we try to add some ideas to the debate in question.
Keywords: subsumption; surplus value; social media; rent; audience labour; prosumer